Od Kresów do pograniczy. Literatura polska XIX i XX wieku na tropach wielokulturowości - Czajkowska, A. (Матеріали до української етнології, 2011)
Kategoria Kresуw w literaturoznawstwie polskim posiada korzenie historyczne i stanowi fenomen kulturowy i aksjologiczny. Wiąże się z ziemiami dawnej Rzeczypospolitej i oznacza tereny dzisiejszych niepodległych Litwy, Białorusi, Ukrainy i Mołdawii, opisywanych w literaturze XIX wieku, a także w wieku XX. Można ją określać jako polonocentryczną, hierarchiczną i monologiczną, choć istnieją elementy wykraczające poza ten sposуb myślenia (np. J.-I. Kraszewski, J. Mackiewicz). Pogranicze jest kategorią wspуłczesną, ktуra zakłada wielokulturowość tamtych ziem i zmienia sposoby interpretowania literatury romantycznej i pуźniejszej. Cechuje ją orientacja na inność, dialogowość i symultaniczność oraz możliwość wykorzystania kontekstu postkolonialnego. The category of the «Kresуw» that is present in the Polish literary studies has historical roots and is a true cultural and axiological phenomenon. It is connected with the territories of the former Republic of Poland and refers to the areas of today’s independent Lithuania, Belarus, Ukraine, and Moldavia, which were presented in the literature of the 19th and 20th centuries. This category can be classified as Poland-centric, hierarchic, and monologic; however, there are certain elements that cross that way of thinking (e. g. J.-I. Kraszewski, J. Mackiewicz). The borderland is a contemporary category, which assumes the multiculturality of those territories and thus changes the ways of interpreting the romantic literature as well as the literature of subsequent times. This category is characterized by its focus on otherness, dialogicality, simultaneity, and the possibility of using the post-colonial context.